2018
DOI: 10.1172/jci121486
|View full text |Cite
|
Sign up to set email alerts
|

TNF overproduction impairs epithelial staphylococcal response in hyper IgE syndrome

Abstract: Autosomal dominant hyper IgE syndrome (AD-HIES), or Job's syndrome, is a primary immune deficiency caused by dominant-negative mutations in STAT3. Recurrent Staphylococcus aureus skin abscesses are a defining feature of this syndrome. A widely held hypothesis that defects in peripheral Th17 differentiation confer this susceptibility has never been directly evaluated. To assess the cutaneous immune response in AD-HIES, we induced suction blisters in healthy volunteers (HVs) and patients with AD-HIES and then ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
(54 reference statements)
5
25
0
Order By: Relevance
“…However, overproduction of these cytokines has detrimental effects on the host, including systemic inflammation and severe tissue damage (42,43). In this study, Etanercept increased survival of TCR -/mice infected by P. aeruginosa, suggesting that the overproduction of TNF in the absence of  T cells contributes to increased mortality.…”
Section: Downloaded Frommentioning
confidence: 53%
“…However, overproduction of these cytokines has detrimental effects on the host, including systemic inflammation and severe tissue damage (42,43). In this study, Etanercept increased survival of TCR -/mice infected by P. aeruginosa, suggesting that the overproduction of TNF in the absence of  T cells contributes to increased mortality.…”
Section: Downloaded Frommentioning
confidence: 53%
“…Viable bacterial colonies were only detectable in the pulmonary tissue of neutropenic mice inoculated with CNS (Figure 4). In contrast, known pathogens such as the methicillin resistant S. aureus (MRSA) isolate USA300-LAC have demonstrated marked pathology in pulmonary and systemic models in wild type mice (Gaidamakova et al, 2012; Myles et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…For example, S. aureus colonization is frequently associated with atopic dermatitis and psoriasis, skin diseases that feature epidermal barrier dysfunction 6568 , and S. aureus may actually contribute to skin inflammation in these patients 69 . Recurrent S. aureus SSTI is also a hallmark of autosomal dominant hyper IgE syndrome (AD-HIES) 70 and it has recently been shown that the impaired epithelial response to infection in these patients results from overproduction of the pro-inflammatory cytokine TNFα 71 . TNFα also contributes to the severity of atopic dermatitis, though TNF blockade by anti-TNF biologicals has thus far failed to improve outcomes in these patients 72 .…”
Section: Discussionmentioning
confidence: 99%